2013
DOI: 10.1080/02699931.2013.781501
|View full text |Cite
|
Sign up to set email alerts
|

Brightness differences influence the evaluation of affective pictures

Abstract: We explored the possibility of a general brightness bias: brighter pictures are evaluated more positively, while darker pictures are evaluated more negatively. In Study 1 we found that positive pictures are brighter than negative pictures in two affective picture databases (the IAPS and the GAPED). Study 2 revealed that because researchers select affective pictures on the extremity of their affective rating without controlling for brightness differences, pictures used in positive conditions of experiments were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
76
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 85 publications
11
76
2
1
Order By: Relevance
“…Research has shown that brightness as compared to darkness is associated both with valence (e.g., Adams & Osgood, 1973;Lakens et al, 2013;Meier et al, 2015) and with activity (Marks, 1978;Mattes et al, 2002;Romaiguère, Hasbroucq, Possamaï, & Seal, 1993). When reviewing these studies, we noticed that whenever associations between brightness and valence were observed, brightness differences were manipulated on a screen or on a piece of paper (e.g., Meier, Robinson, & Clore, 2004), while studies that revealed an association between brightness and activity manipulated brightness using a light fixture (e.g., Romaiguère et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has shown that brightness as compared to darkness is associated both with valence (e.g., Adams & Osgood, 1973;Lakens et al, 2013;Meier et al, 2015) and with activity (Marks, 1978;Mattes et al, 2002;Romaiguère, Hasbroucq, Possamaï, & Seal, 1993). When reviewing these studies, we noticed that whenever associations between brightness and valence were observed, brightness differences were manipulated on a screen or on a piece of paper (e.g., Meier, Robinson, & Clore, 2004), while studies that revealed an association between brightness and activity manipulated brightness using a light fixture (e.g., Romaiguère et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…In the current set of studies, we focus on the concept of aggression, which compared to calmness forms the plus pole on the activity dimension, but the minus pole on the evaluation dimension (Russell & Mehrabian, 1977). Brightness is more active, and more positive, compared darkness, and thus forms the plus pole on both the activity and the evaluation dimension, whereas darkness forms the minus pole on the activity and evaluation dimension (e.g., Adams & Osgood, 1973;Lakens et al, 2013;Marks, 1978;Mattes, Leuthold, & Ulrich, 2002;Meier, Fetterman, & Robinson, 2015). If polarity correspondence is indeed a mechanism in cross-modal associations, it is essential to predict along which specific dimension aggression-calmness becomes aligned with a second pair of concepts.…”
Section: Dimensions Of Meaningmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies convincingly show that the task specific context can influence the associative meaning of a concept in a task (e.g., Blair 2002;Elliot & Maier, 2014;Frühholz, Trautmann-Lengsfeld, & Herrmann, 2011;Lakens, Fockenberg, Lemmens, Ham, & Midden, 2013). For example, studies suggest that in an achievement context, red is associated with failure and negativity (e.g., Moller, Elliot, & Maier, 2009), while in a romantic context, red is associated with attraction and excitement (e.g., Elliot & Pazda, 2012).…”
mentioning
confidence: 99%
“…For instance, quite strong associations exist between brightness and goodness (morality) but also activity and liveliness, in contrast to how darkness is generally associated with immorality and, to a lesser extent, inactivity (Schietecat et al 2018a). Acting like contextual cues that impact information processing, such cognitive associations may result in approach or avoidance behaviors (e.g., Mehta and Zhu 2009), more positive or negative appraisals of objects or scenes (Beute and de Kort 2013;Lakens et al 2013), different styles of information processing (Steidle et al 2011), and different social perceptions and moral behavior (e.g., Baron et al 1992;Schietecat 2018;Zhong et al 2010), resulting, for instance, in more positive assessments of written personnel folders of fictive employees under dimmer conditions but also more dishonest reporting of one's performance on a task and persons photographed in dimmer conditions being judged less positive and more aggressive than the same individuals photographed in bright conditions. These studies imply that, through associative pathways, light not only changes the way we perceive spaces and the objects and persons in them but also how we assess those objects, tasks, and other persons and how we relate to them.…”
Section: Visual Experiencementioning
confidence: 99%